PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), AUDITOR SWITCHING DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2022 – 2024 - Siti Annisah Setiawan Sinaga; Darni; Cindy Claudia Manalu; Evelyn; Tiorika Nababan; Ananda Anugrah Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Indonesia Stock Exchange (IDX) is vital in assisting companies in raising capital through the issuance of securities, in addition to providing a platform for investors. The IDX oversees and regulates the capital market, making sure that all trading is done fairly, efficiently, and transparently. The audit delays of food and beverage manufacturing companies listed on the IDX from 2022 to 2024 will be analyzed. Examples of such variables include business size, auditor change, debt-to-equity ratio, and return on assets. The study population comprised 56 companies, with a sample size of 168 observations. Audit delays were positively and significantly affected by return on assets and auditor change, whereas the debt-to-equity ratio exhibited a negative and insignificant impact. A robust negative correlation exists with company size. Return on assets, auditor change, debt-to-equity ratio, and company size exhibited positive and statistically significant impacts on audit delays in concurrent analyses.